Groundwater Contamination by Leachate from Landfill and Open ‎Dumpsite of Solid Waste: A Review ‎ (Journal of University of Babylon for Engineering Sciences, 2025)
This research attempts to review most of the studies of groundwater contamination near landfills, mainly arising from un-engineered landfills or open dumps overseas, and its influence on human health. Leachate water from landfills contains various types of municipal toxic wastes as well as heavy metals, which eventually seep into the ground and infiltrate the groundwater table. Consumption of such water causes severe health risks and can occasionally be lethal if consumed over lengthy periods of time. Several investigations have demonstrated indications of significant quantities of heavy metals in both leachate water and surrounding groundwater sources. In addition, the environmental impacts of leachate on groundwater quality are critically analyzed, focusing on the Leachate Pollution Index (LPI) and the Canadian Water Quality Index (CCME WQI) as tools for assessing contamination levels. Finally, It is recommended that all open waste dumps be removed and engineered waste dumps be established in accordance with approved environmental specifications. Furthermore, the generated leachate should be collected by constructing wells from which the leachate should be diverted to a basin (with a suitable lining system) for treatment.